Maize beer production in Middle Horizon Peru - Valdez, Lidio M. (My University, 2006)
When the Spaniards marched into the Inka capital of Cuzco in 1533, chicha (maize beer) was the common, everyday beverage within the vast Inka empire. Recent archaeological research carried out at Marayniyoq, a Middle Horizon Wari site in the Ayacucho Valley in central Peru, uncovered a series of cut stones with hollow depressions. Several features of these artifacts indicate that they functioned as grinding stones. Confirming this observation is the finding in association with the cut stones of several rocker grinders or milling stones, which are the active elements of grinding equipment. While this evidence convincingly indicates that grinding was an important activity at the site, fieldwork also uncovered a large number of large vessels. Most of these vessels had been broken and then repaired in the distant past, a fact which suggests that they were used for storing dry products that perhaps were processed by means of the grinding stones. The evidence from Marayniyoq is very similar to artifacts associated with maize beer production during (later) Inka times, strongly indicating that during the Middle Horizon maize beer appears to have been produced in a fashion very similar to that of the Inka. At the same time, this evidence suggests that maize beer distribution was a function of the state, perhaps as part of reciprocal obligations between elites and commoners.
Keywords: brewing; maize beer; Middle Horizon Peru